Pengaruh Return On Assets (ROA), Return On Equity (ROE), Debt To Equity Ratio (DER) dan Earning Per Share (EPS) terhadap Tingkat Underpricing pada Perusahaan yang Melakukan Initial Public Offering (IPO) di Bei Tahun 2022 - Muhammad Alwi Siraj; Ujang Syahrul Mubarrok; Beni Mahyudi S (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the influence of Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Earnings Per Share (EPS) on the level of underpricing in companies conducting an Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) during 2022. Underpricing, a condition where the initial offering price of a stock is lower than its secondary market price, is a critical concern as it can affect the effectiveness of capital raising through IPOs. Using data from non-financial companies that went public in that year, this research identifies financial factors contributing to the level of underpricing and their implications for investors and companies. This study employs a quantitative descriptive research method. The objects of this research are companies that conducted IPOs on the IDX. The population consists of 57 companies, and the sample includes 52 companies that meet the specified criteria. The data analysis is conducted using SPSS software. The results show that ROA has a negative but not significant effect on underpricing, ROE has a negative but not significant effect on underpricing, DER has a negative but not significant effect on underpricing, while EPS has a positive and significant effect on underpricing. Simultaneously, ROA, ROE, DER, and EPS have a significant effect on underpricing.